PENGARUH PENGAWASAN AKUNTABILITAS TERHADAP KINERJA MANAJEMEN PADA RUMAH SAKIT UMUM SAKINAH KOTA LHOKSEUMAWE - Bobby Rahman; Zulkarnaini Zulkarnaini (LPPM STIE Lhokseumawe, 2017)
The purpose of research is to determine how much influence accountability monitoring the performance of management in public hospitals Sakinah Lhokseumawe city. Data used in the form of primary data obtained or collected from direct observations of employees of the General Hospital Sakinah Lhokseumawe City. The data processing is done with the help of a simple regression model were processed using the SPSS program. The results showed that significantly influence the accountability monitoring management performance Sakinah General Hospital Lhokseumawe city. Performance Management at the General Hospital Lhokseumawe city Sakinah able to be explained by variables accountability monitoring, as more and better oversight of accountability is applied it will be followed by further achievement of the management of the Hospital was clean, fair, transparent and accountable.